Where Exactly Are All the First Nation Businesses? Interpreting the First Nation Business Environment in the Yukon, 2008-2021 - Coates, Kenneth; Finnegan, Greg (Journal of Aboriginal Economic Development, 2024)
The Yukon has one of the fastest growing, albeit smallest, economies in Canada, with an increasing population and a tight labour market. Modern treaties and self-government agreements have empowered First Nations governments, and Supreme Court decisions and treaty rights secured Indigenous governments a significant place in the resource sector. Yet Yukon First Nation businesspeople are not yet benefiting fully from this positive political and economic situation. This paper explores the underrepresentation of the Yukon First Nation businesspeople in the economy by examining the available data from the Yukon Business Survey (YBS), a census of Canada self-employment data, and a new national program at Statistics Canada that is working to better identify the presence of Indigenous businesses within the national economy. The research shows that work still needs to be done to better support the development of Indigenous businesspeople as they strive to break through the barriers that have left them on the margins of the northern economy.